A brief study on the unique form, representation and utility of masks in the Vaisnavite monasteries of Assam - NILANJANA GOGOI (Journal of Advanced Research in Social Sciences and Humanities, 2016)
Aim: This study draws from archival materials and theoretical perspectives. The Vaisnavite Masks are an attempt to find a voice in the conventional medium that pushes back against the kind of stereotyping, high/low art, or classical art that is so prevalent in contemporary urban culture.Method: The present research uses a descriptive method to present its data. The information gathered was based on the papers written before now. The results were obtained by comparing various variables.Findings: The audience’s thought processes are altered by the combination of the elaborate costumes and make-up with the unique communicative language (Brajawali) spoken between the performers. It gives them a fantastical, exciting visual experience of the show. The audience members’ minds are manipulated into experiencing an emotional investment and agitation as they watch the performance.Implications/New Approach: The creation of masks is a significant form of medium that captures and gives us visual narrative representations of historical and current data. The occupation of galleries over the common people’s visual psyche has been challenged by its distinctive forms, utility, and structural representations, which challenge the hierarchical practices of mainstream arts.